Comparison of thinprep™ monolayer cytology versus conventional pap smear and the correlation with human papilloma virus detection using hybrid capture® 2 system - Ma'asah, Mohd. Shariman Md. Shah @ (2007)
Pap smear is a useful screening tool for cancer of the cervix. Screening has resulted in the tremendous fall in cervical cancer incidence worldwide. However, the conventional pap smear has many limitations due to significant false negative and false positive rate, and unsuitability due to thick smears. Liquid-based cytology, such as ThinPrep™ technique is an alternative to conventional pap smear. This method provides monolayer cells which make cytological examination easier. HPV is the cause of cervical cancer. Identification of the virus is helpful in cervical cancer screening. Hybrid Capture® 2 systems is one of the examples of HPV testing that is useful to detect high-risk HPV in a large number of samples. We embarked on pap smear split-sampling study to determine if monolayer cytology would give better results than conventional cytology. Six hundred eighty eight women who gave consent were recruited. We collected the exfoliative cervical samples from all the subjects. Each sample was smeared as for the conventional pap smears as done routinely and then rinsed into a liquid buffer (PreservCyt) for monolayer cytology and HPV testing. The cytological examination was performed in blinded fashion. The performance of conventional and ThinPrep TM monolayer cytology pap smears was compared. Smears were classified based on The 2001 Bethesda classification. All cases which had epithelial abnormalities were further tested for HPV by Hybrid Capture® 2 technique. We found that adequacy of sampling was 94.3% in conventional pap smear and 89.4% in TbinPrep™ monolayer cytology. The commonest organism identified was Candida spp (4.1% in conventional smears, 3.9% by ThinPrepTM) and the agreement study is fair (k=0.27). Diagnosis of ASCUS, LSIL, HSIL and squamous cell carcinoma, were low in both techniques. The glandular cells abnormalities were also low in numbers. The agreement studies for LSIL showed k=0.40. The agreement studies for ASCUS, HSIL, squamous cell carcinoma, AGC (NOS) and adenocarcinoma (NOS) were not done as the number was too few. The HPV testing of cases with abnormal cytology showed low positivity (38.5%). The overall performance of ThinPrep™ is no better than conventional pap smears. The usage of the ThinPrep™ pap smear does not improve in detecting certain infective organisms nor abnormal epithelial cells. The low positivity of Hybrid Capture® 2 technique is questionable. Confirmation with other techniques like PCR is essential. In conclusion, split sampling gives adequate smears for cytological assessment. It can be carried out in laboratories working to change from one technique to another.